Effects of ractopamine (paylean) dose and feeding duration on pig performance in a commercial finishing facility - Main, R.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,035 gilts were used in a 28- day trial conducted in a commercial research facility to determine the influence of ractopamine (PayleanTM) dose (4.5 or 9.0 g/ton) and feeding duration (7, 14, 21, or 28 days prior to slaughter) on pig performance and carcass composition. Ractopamine supplementation at 4.5 g/ton for 14 to 28 days, and 9 g/ton for 7 to 28 days, improved (P<0.05) ADG by 26 to 35% (0.35 - 0.46 lb/d) and F/G by 16 to 20% (0.64 to 0.79) during the 28-days prior to slaughter. Due to these improvements in growth, carcass weights increased 8 to 10 pounds over controls. Fat depth and lean percentage improved (linear, P<0.01) with increased feeding duration. Ractopamine dose did not affect carcass lean parameters. However, carcass yield improved (P< 005) when ractopamine was fed at 9.0 g/ton. Feed cost per pound of gain increased (P<0.01) with increasing feeding duration for Paylean and was greater (P<0.05) for pigs fed the 9.0 g/ton dose for 28 days as compared to the control. However, feeding ractopamine at 4.5 g/ton for 14 to 28 days and 9 g/ton for 7 to 28 days improved income over feed costs by $3.53 to $ 4.76 per head compared to pigs fed the control diet. Return over feed costs improved due to the increased carcass weights and improved feed efficiency with the greatest values achieved with a 14 to 21 day feeding duration. These data indicate feeding ractopamine at either 4.5 or 9.0 g/ton for 14 to 21 days prior to slaughter is a cost-effective strategy to optimize return while minimizing increases in feed cost per pound of gain.
Keywords: Swine; Ractopamine; Paylean; Economics